Pemanfaatan Limbah Botol Plastik sebagai Media Tanam Hidrobokas di Desa Putak, Kecamatan Gelumbang, Muara Enim: Utilization of Plastic Bottle Waste as Hydrobokas Planting Media in Putak Village, Gelumbang District, Muara Enim Regency - Puspitahati, Puspitahati; Oktarina, Selly; Saputra, Daniel; Triana, Arjuna Neni; Panggabean, Tamaria; Agustina, Hilda; Hower, Haisen; Prima, Fidel Harmanda; Robbani, Syifa'; Aulia, Nurul Izzah; Haryani, Fatria Resti; Setyaaji, Primayoga Harsana; Oktarina, Della (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Community service activities in Putak Village aim to educate and empower farmers and housewives in utilizing plastic bottle waste as a medium for planting hydroboks technology for vegetable crops through a simple hydroponic system (NFT). This program is carried out for five months through the stages of field surveys, counseling, technical training, mentoring, and evaluation. The results of the activity show the effectiveness of the use of plastic waste as an environmentally friendly and sustainable planting medium, helping to reduce the pile of plastic waste while providing urban farming solutions in narrow yards. This training successfully improved the community's knowledge and technical skills about hydrobacca systems, which is evident from the enthusiasm of the participants and their success in growing vegetables independently. In addition, this program has a positive impact on the economy by reducing spending on purchasing vegetables and supporting the consumption of pesticide-free fresh food. The environmental impact is also seen through increasing public awareness in managing plastic waste based on the 3R (Reduce, Reuse, Recycle) principle. The success of this program can be increased through continuous education, such as seminars, plastic waste management innovation competitions, and the creation of educational materials in the form of videos and posters to reach more bans.